Dispersal of juvenile leatherback turtles from different Caribbean nesting beaches: A model study - Gaspar, Philippe; Candela, Tony; Shillinger, George L. (Frontiers in Marine Science, 2022)
The Northwest Atlantic (NWA) leatherback turtle (Dermochelys coriacea) subpopulation was recently classified as endangered. It nests in the Wider Caribbean Region and includes 5 genetic stocks, all declining albeit at different rates. The causes of decline are multiple and difficult to identify based on annual nest counts which integrate the effects of multiple stressors over the entire life history. Demographic models however show that survival during the juvenile pelagic stage is a main factor modulating population trends, but this life stage remains largely unobserved. This paper presents a suite of numerical simulations where juveniles from the five NWA stocks disperse under the combined effects of ocean currents and habitat-driven swimming movements. Simulations reveal when and where NWA juveniles likely disperse and thus the environmental conditions and anthropogenic threats they may encounter. Simulated individuals initially disperse following either the “Caribbean route”, inside the Caribbean Sea and the Gulf of Mexico (GoM), or the “Atlantic route” east of the Antilles Islands Arc. The percentage of individuals following one or the other route varies markedly with the stock of origin. Late dispersal in the eastern Atlantic Ocean and Mediterranean Sea is similar in all stocks. Juveniles having followed the Caribbean route are rapidly entrained northwards by the Gulf Stream and incur a high risk of cold-induced mortality. This mostly affects the Florida stock and the Western Caribbean (WCA) stock nesting in Costa Rica, Panama and Colombia. The Atlantic route is less lethal as individuals progress more slowly towards higher latitudes. Simulations also show that the percentage of WCA juveniles visiting the GoM is larger than for any other stock. Following the Learned Migration Goal hypothesis, which posits that adult sea turtles tend to exploit foraging areas that they previously identified at the juvenile stage, this may explain why WCA adults are overrepresented in the GoM. Finally, our results suggest that the recently observed increase in the percentage of WCA adults migrating into the GoM could be linked to bycatch reduction measures implemented in 2003-2004, combined with an increase in the frequency of Loop Current intrusion and eddy-shedding events that started around year 2000.